Information and Communication Technologies in Education, Research, and Industrial Applications : 14th International Conference, ICTERI 2018, Kyiv, Ukraine, May 14-17, 2018, Revised selected papers /: 14th International Conference, ICTERI 2018, Kyiv, Ukraine, May 14-17, 2018, Revised selected papers. (2019) - Unknown
No abstract available